Periodic concentration–polarization-based formation of a biomolecule preconcentrate for enhanced biosensing. Issue 46 (19th November 2020) - Park, Sinwook; Buhnik-Rosenblau, Keren; Abu-Rjal, Ramadan; Kashi, Yechezkel; Yossifon, Gilad
Abstract : Periodic concentration–polarization-based formation of a preconcentrated biomolecule plug using the sandwich immunoassay approach, wherein the target biomolecules bind between immobilized magnetic bead-conjugated antibodies and reporter antibodies. Abstract : Ionic concentration–polarization (CP)-based biomolecule preconcentration is an established method for enhancing the detection sensitivity of target biomolecules. However, the formed preconcentrated biomolecule plug rapidly sweeps over the surface-immobilized antibodies, resulting in a short-term overlap between the capture agent and the analyte, and subsequently suboptimal binding. To overcome this, we designed a setup allowing for the periodic formation of a preconcentrated biomolecule plug by activating the CP for predetermined on/off intervals. This work demonstrated the feasibility of cyclic CP actuation and optimized the sweeping conditions required to obtain the maximum retention time of a preconcentrated plug over a desired sensing region and enhanced detection sensitivity. The ability of this method to efficiently preconcentrate different analytes and to successfully increase immunoassay sensitivity underscore its potential in immunoassays serving the clinical and food testing industries.